Inovasi Teknik Membatik Rizky Juniyanto Pada Produk Properti Seni Pertunjukan - Pratiwi, Intan; Sekar Suci Nirmala, Komang (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Indonesia has many tribes and cultures, which create various works of art and culture. The enthusiasm of the community in preserving culture has enabled this culture to develop to this day. Artists become more creative and innovative in their work because of the public's enthusiasm for works of art. Artists must have talent and strong determination. Arts in Indonesia, such as Performing Arts and Fine Arts, can be an opportunity for artists to collaborate and develop culture. Performing Arts involves Dance, Dramatic Arts, and Musical Arts, while Fine Arts involves Sculpture, Ceramic Arts, Painting, and Craft Arts. Props and costumes are used in performing arts works, depending on the theme and title of the work to be created. Props such as shawls, plates, umbrellas, fans, trees and stones are used to depict the atmosphere in the performance. Performing Arts and Craft Artists can collaborate with each other for mutual benefit. Rizky Juniyanto is a young Craft Artist who has a variety of batik works, including earthenware batik, cloth batik, umbrella batik, and wooden batik. His works not only function as decoration, but also as everyday objects such as teapots, pans, glasses, plates, savings and jars made of earthenware. These products have high aesthetic and selling value. Rizky Juniyanto also accepts orders for souvenirs and performing arts props. He markets his work through online sites and applications and collaborates with several studios. Apart from producing works of art, Rizky Juniyanto often fills workshops and teaches other people how to make his works to develop craft art. Keywords: Property, Art, Artists.